Evidence of biologic epistasis between BDNF and SLC6A4 and implications for depression - Pezawas, L; Meyer-Lindenberg, A; Goldman, A L; Verchinski, B A; Chen, G; Kolachana, B S; Egan, M F; Mattay, V S; Hariri, A R; Weinberger, D R (Molecular psychiatry, 2008)
Complex genetic disorders such as depression likely exhibit epistasis, but neural mechanisms of such gene–gene interactions are incompletely understood. 5-HTTLPR and BDNF VAL66MET, functional polymorphisms of the serotonin (5-HT) transporter ( SLC6A4 ) and brain-derived neurotrophic factor ( BDNF ) gene, impact on two distinct, but interacting signaling systems, which have been related to depression and to the modulation of neurogenesis and plasticity of circuitries of emotion processing. Recent clinical studies suggest that the BDNF MET allele, which shows abnormal intracellular trafficking and regulated secretion, has a protective effect regarding the development of depression and in mice of social defeat stress. Here we show, using anatomical neuroimaging techniques in a sample of healthy subjects ( n =111), that the BDNF MET allele, which is predicted to have reduced responsivity to 5-HT signaling, protects against 5-HTTLPR S allele-induced effects on a brain circuitry encompassing the amygdala and the subgenual portion of the anterior cingulate (rAC). Our analyses revealed no effect of the 5-HTTLPR S allele on rAC volume in the presence of BDNF MET alleles, whereas a significant volume reduction ( P <0.001) was seen on BDNF VAL/VAL background. Interacting genotype effects were also found in structural connectivity between amygdala and rAC ( P =0.002). These data provide in vivo evidence of biologic epistasis between SLC6A4 and BDNF in the human brain by identifying a neural mechanism linking serotonergic and neurotrophic signaling on the neural systems level, and have implications for personalized treatment planning in depression.